(untitled) (Bangladesh Journal of Medical Microbiology, 2025)
Background: There are more than 10 families of genes associated with ESBL, among them the highest number of variants corresponds to the CTX-M family. Gene encoding CTX-M (blaCTX-M) has several allelic variants, which has different geographical distributions. Objective: The aim of the study was to detect distribution of blaCTX-M gene among multidrug resistant Escherichia coli and Klebsiella species along with it’s subtypes among different clinical samples. Methodology: Isolation and identification of Escherichia coli and Klebsiella species was done from clinical isolates sent for culture and sensitivity test at Department of Microbiology and Immunology in Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh by using Standard Operating Procedure. Antibiotic susceptibility testing was done by Kirby Bauer disk diffusion method. Then multidrug resistant Escherichia coli and Klebsiella species were identified and phenotypic detection of ESBL was done by Double Disc Synergy Test. After that, blaCTX-M gene among the multidrug resistant organisms was identified using polymerase chain reaction (PCR). Then variants of blaCTX-M gene were identified by Sanger sequencing. Results: In this study, total 60 multidrug resistant laboratory isolates were collected and most of the multidrug resistant organisms were isolated from urine 30(50%), followed by wound swab 11(18.3%), sputum 10(16.7%), blood 7(11.7%) and pus 2(3.3%). Amoxicillin, cefuroxime, cefotaxime and ceftriaxone were resistant in all isolates. No resistance was found in meropenem. Twenty-three(38.3%) isolates were positive in phenotypic ESBL confirmatory test by DDST. But PCR assay showed 50(83.3%) isolates have blaCTX-M gene. Sanger sequencing of the blaCTX-M positive isolates showed that most common variant of CTX-M is CTX-M-15, which is 39(78.0%), followed by CTX-M-14, 6(12.0%) and CTX-M-3, 5(10.0%) in number. Conclusion: In conclusion, high prevalence of blaCTX-M gene was found among MDR Escherichia coli and Klebsiella species with different variations Bangladesh Journal of Medical Microbiology, January 2025;19 (1):46-53